Electron Bio‐Imaging Centre (eBIC): the UK national research facility for biological electron microscopy. Issue 6 (5th June 2017) - Clare, Daniel K.; Siebert, C. Alistair; Hecksel, Corey; Hagen, Christoph; Mordhorst, Valerie; Grange, Michael; Ashton, Alun W.; Walsh, Martin A.; Grünewald, Kay; Saibil, Helen R.; Stuart, David I.; Zhang, Peijun
Abstract : This paper provides an introduction to the Electron Bio‐Imaging Centre (eBIC) at Diamond Light Source: an external user facility established in the UK for high‐end cryo‐electron microscopy. Details are given of the first year of operation along with highlights and future challenges. Abstract : The recent resolution revolution in cryo‐EM has led to a massive increase in demand for both time on high‐end cryo‐electron microscopes and access to cryo‐electron microscopy expertise. In anticipation of this demand, eBIC was set up at Diamond Light Source in collaboration with Birkbeck College London and the University of Oxford, and funded by the Wellcome Trust, the UK Medical Research Council (MRC) and the Biotechnology and Biological Sciences Research Council (BBSRC) to provide access to high‐end equipment through peer review. eBIC is currently in its start‐up phase and began by offering time on a single FEI Titan Krios microscope equipped with the latest generation of direct electron detectors from two manufacturers. Here, the current status and modes of access for potential users of eBIC are outlined. In the first year of operation, 222 d of microscope time were delivered to external research groups, with 95 visits in total, of which 53 were from unique groups. The data collected have generated multiple high‐ to intermediate‐resolution structures (2.8–8 Å), ten of which have been published. A second Krios microscope is now in operation, with two more due to come online in 2017. In the next phase of growth of eBIC, in addition to more microscope time, new data‐collection strategies and sample‐preparation techniques will be made available to external user groups. Finally, all raw data are archived, and a metadata catalogue and automated pipelines for data analysis are being developed.